Evidence-based policy making in the social sciences : methods that matter - Stoker, Gerry; Evans, Mark, 1965 February 17- (Bristol, UK : Policy Press, 2016)
Drawing on the insights of some of the world's leading authorities in public policy analysis, this important book offers a distinct and critical showcase of emerging forms of discovery for policy-making. Chapter by chapter this expert group of social scientists showcase their chosen method or approach, showing the context, the method's key features and how it can be applied in practice, including the scope and limitations of its application and value to policy makers. Arguing that it is not just econometric analysis, cost benefit or surveys that can do policy work, the contributors demonstrate a range of other methods that can provide evidenced-based policy insights and how they can help facilitate progressive policy outcomes. The book will be ideal for upper level undergraduate students as well as Public Policy post-graduates, and can be used as the basis of an intensive learning experience for policy makers.--
Introduction / Gerry Stoker, Mark Evans -- 1. Evidence-based policy making and social science / Gerry Stoker, Mark Evans -- 2. Crafting public policy : choosing the right social science method / Gerry Stoker, Mark Evans -- 3. Systematic reviews for policy / David Gough, Janice Tripney -- 4. Randomised controlled trials / Peter John -- 5. Qualitative comparative analysis for reviewing evidence and making decisions / Matt Ryan -- 6. Narrative and storytelling / Vivien Lowndes -- 7. Visuals in policy making : "see what I'm saying" / Leonie J. Pearson, Lain Dare -- 8. "Big data" and policy learning / Patrick Dunleavy -- 9. Cluster analysis in policy studies / Jinjing Li -- 10. Microsimulation modelling and the use of evidence / Robert Tanton, Ben Philipps -- 11. Citizen social science and policy making / Liz Richardson -- 12. Deliberative policy analysis / John S. Dryzek -- 13. Co-design with citizens and stakeholdres / Mark Evans, Nina Terrey -- Conclusion : connecting social science and policy / Gerry Stoker, Mark Evans.
"This book emerged out of a conference that took place on Thursday 19 and Friday 20 February 2015 at Old Parliament House, Canberra, Australia"--Page xiii
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Policy sciences -- Congresses; Social sciences -- Congresses; Sciences de la politique -- Congrès.; Sciences sociales -- Congrès.; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Public Affairs & Administration; Policy sciences; Social sciences; Politischer Prozess; Forschungsmethode; Sozialwissenschaften; Politische Entscheidung; Electronic books; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.